CHALLENGES ENCOUNTERED IN RELIGIOUS EDUCATION IN TURKEY - Demircioğlu, Aytekin (Journal of Education Culture and Society, 2020)
Aim. In this study, the challenges encountered during the introduction of religious education in Turkey are examined within the scope of their intended solutions.Methods. In this study, challenges encountered in the implementation of religious education in Turkey are being discussed in a descriptive manner. Literature scanning and interpretation methods, one of the qualitative research methods, were used in the study. Results. Religious education in Turkey is both maintained within the formal education system and the non-formal education system. Formal education is provided in public schools run by the Ministry of National Education [MNE]. Primary, secondary and high school education is compulsory for all students. There are Imam Hatip Schools that were opened to provide religious education at secondary and high school level. There are also two hours of compulsory religious education per week in other schools. Non-formal religious education is provided only by the Presidency of Religious Affairs [PRA]. This training is given to people of all ages. For this purpose, the PRA opens several courses.Conclusions. In this study, challenges encountered related to religious education in Turkey are being discussed in two main areas: Challenges in formal education are examined under seven subtitles. Challenges in non-formal education are examined under eight subtitles.Originality. This study is an original study in terms of addressing the challenges in formal and non-formal religious education together. In addition, the possibility of making a collective examination of challenges related to religious education in Turkey would be valuable to the reader.